2010
DOI: 10.1038/msb.2010.80
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the evolution of phagosomes

Abstract: First large-scale comparative proteomics/phosphoproteomics study characterizing some of the key steps that contributed to the remodeling of phagosomes that occurred during evolution. Comparison of profiling analyses of isolated phagosomes from three distant organisms (Dictyostelium, Drosophila, and mouse) revealed a protein core that defines a potential ‘ancient' phagosome and a set of 50 proteins that emerged while adaptive immunity was already well established.Gene duplication events of mouse phagosome paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
149
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 66 publications
3
149
0
Order By: Relevance
“…SHP-1 has previously been shown to associate with phagosomes, raising the possibility that it participates in the biogenesis of phagolysosomes (21,22). To investigate a potential role for SHP-1 in this process, we first performed confocal immunofluorescence experiments to visualize SHP-1 redistribution in murine BMM upon phagocytosis of serum-opsonized zymosan particles (27)(28)(29).…”
Section: Shp-1 Is Recruited To Nascent Phagosomes and Remains Throughmentioning
confidence: 99%
See 2 more Smart Citations
“…SHP-1 has previously been shown to associate with phagosomes, raising the possibility that it participates in the biogenesis of phagolysosomes (21,22). To investigate a potential role for SHP-1 in this process, we first performed confocal immunofluorescence experiments to visualize SHP-1 redistribution in murine BMM upon phagocytosis of serum-opsonized zymosan particles (27)(28)(29).…”
Section: Shp-1 Is Recruited To Nascent Phagosomes and Remains Throughmentioning
confidence: 99%
“…2D). To determine whether known SHP-1 substrates were differentially phosphorylated and recruited to phagosomes in the absence of SHP-1, we focused on Dok-1 (p62 Dok ), a major SHP-1 substrate (32) present in the phagosome proteome (22). Western blot analyses revealed that Dok-1 levels in phagosome lysates increased progressively over time, independently of the presence of SHP-1 (Fig.…”
Section: Shp-1 Is Recruited To Nascent Phagosomes and Remains Throughmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main functions of macrophages is phagocytosis, which is the active uptake of large particles (> 0.5 μm) by cells 3. Phagocytosis is an important cellular mechanism for almost all eukaryotes, highly conserved from amoeba to human 4, in mammals, it is a key part of the innate immune response against invading microorganisms. Moreover, macrophages phagocytose apoptotic cells and cell debris to recycle cellular building blocks during homeostasis and development 5, 6.…”
mentioning
confidence: 99%
“…In recent years, the cell line has also been used extensively in proteomics experiments including a large‐scale proteome 10, phagosome proteomics 4, 8, 11, responses to cytokines 12, 13, and identification of DNA receptors 14.…”
mentioning
confidence: 99%